SOFTWARE EN MATLAB PARA UN SISTEMA DE ADQUISICIÓN DE DATOS UTILIZANDO LA TARJETA DE SONIDO DE UNA PC. - Jiménez Tintaya, César Ornar (2005)
Given the high cost of cards of data acquisition, it has been designed and implemented a system of data acquisition by means of the sound card of the PC, which is a digital analogical converter of 2 channels, with a resolution of 16 bits and one frequency of sampling of 1Hz up to 44,1 kHz. The cost is relatively low or practically null, because most of the PC present they have a sound card. The graphical interface of user has been implemented in Matlab, with options to select the number of channels, 1 number of bits, frequency of sampling and time of recording. The signa! is graficada as much in the dominion of the time like in the dominion of the frequency via transformed his of Fourier. Also an option is included to make the filtrate of the signa!, to reproduce the signa!in case of working with frequencies of audio and other utilities. This system can be applied to the digital signa! processing of audio, certain experiments of laboratory, acquisition of seismic signals, acquisition of biomedical signals, oscilloscope of LF, etc. To the advantages and disadvantages of the acquisition system are discussed.